UF/IFAS Nutrient Management Recommendation Series: Strawberry: SL517/SS730, 9/2024 - Agehara, Shinsuke; Obreza, Tom; Mylavarapu, Rao (EDIS, 2024)
Nutrient management recommendations for strawberry are described according to the standard UF/IFAS recommendation format of 1) a calibrated soil test result; 2) target soil pH; 3) the "4Rs" of fertilizer management: rate, timing, placement, and source; and 4) water management factors.